2009
DOI: 10.1007/s10681-009-9990-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a high-density SSR marker-based linkage map of zoysiagrass (Zoysia japonica Steud.)

Abstract: A consensus genetic linkage map with 447 SSR markers was constructed for zoysiagrass (Zoysia japonica Steud.), using 86 F 1 individuals from the cross 'Muroran 2' 9 'Tawarayama Kita 1'. The consensus map identified 22 linkage groups and had a total length of 2,009.9 cM, with an average map density of 4.8 cM. When compared with a previous AFLP-SSR linkage map, the SSR markers from each linkage group mapped to similar positions in both maps. Eight pairs of linkage groups from the AFLP-SSR map were joined into ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
0
28
1
Order By: Relevance
“…More recently, high-density genetic linkage maps have been constructed for zoysiagrass using AFLP and SSR markers (Cai et al 2004, Li et al 2009). In zoysiagrass, morphological characteristics that can be visually assessed are important factors when determining turf quality, while QTLs for tolerance of environmental stressors such as salinity and freezing may be widely distributed among species.…”
Section: Zoysiagrass (1) Characteristics and Recently Released Cultivarsmentioning
confidence: 99%
“…More recently, high-density genetic linkage maps have been constructed for zoysiagrass using AFLP and SSR markers (Cai et al 2004, Li et al 2009). In zoysiagrass, morphological characteristics that can be visually assessed are important factors when determining turf quality, while QTLs for tolerance of environmental stressors such as salinity and freezing may be widely distributed among species.…”
Section: Zoysiagrass (1) Characteristics and Recently Released Cultivarsmentioning
confidence: 99%
“…The length of the new genetic linkage map was 2,158.5 cM and was extended up to 148.6 cM as compared with the previously published map (Li et al 2009). The map distance in the present study is longer than all zoysiagrass genetic maps reported previously (Ebina et al 1999;Yaneshita et al 1999;Cai et al 2004Cai et al , 2005Li et al 2009), it was even longer than that b Fig.…”
Section: New Linkage Map Based On Ssr Rflp Cisp and Plug Markersmentioning
confidence: 75%
“…The true F 1 plants, confirmed using two SSR markers with different heterozygous alleles in both parents, were used as a mapping population (Li et al 2009). …”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations